Citizenship in times of datafication and infocracy - Ramos Chávez, Alejandro (Revista General de Información y Documentación, 2024)
Within the framework of the debate about the quality of democracy and citizenship participation, this article analyses digitalization processes and the explosion in the importance currently given to the use of data in personal and collective decision making. While these technologies open a wide range of possibilities that allow digital citizens to obtain information – including new channels of interaction between citizens, as well as citizens and the government – we should look at the flipside of this and not limit ourselves to the idealized analysis of the processes. In this sense, the enormous availability of information that citizens have in the palm of their hand also leads to phenomena such as infocracy, where deliberative spaces that allow for the enrichment and plurality of ideas are lost. Instead of deliberation, we observe processes of closing in, an absence of acknowledgment of the other, and the increasingly common construction of ideas and beliefs far from the truth – all of which degrade democracy.